INTEGRATION OF ARTIFICIAL INTELLIGENCE IN MEDICAL EDUCATION: A PROSPECTIVE OBSERVATIONAL STUDY - Siyyar ahmad; Ihtisham ul Haq; Ayaz ul haq; Naveed Iqbal; Ijaz ahmad (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: AI is being embraced in Medical Education by creating Virtual Reality applications to improve students’ learning and practical skills. Traditional approaches for employee training do not always feature the above components which shows that AI can be useful in this area. Objectives: Hypothesis To assess the effect of training through artificial intelligence on the improvement of medical students’ knowledge and skills, and confidence in the Khyber medical college Peshawar in collaboration Khyber Medical University. Methods: The respondents were one hundred medical students from Khyber medical college Peshawar in collaboration Khyber Medical University who undertook an AI-based training from February 2022 to July 2022. These were modules of anatomy, surgical and emergencies and all were AI based simulations. Knowledge assessment before and after training involved theoretical tests, practical assignments and participants’ feedback. Results: The participants comprised 100 students with a mean age of 22. 5 years or 2. 3 years’ deviation. The retention of knowledge went up by 35% with values < 0. 01. Therefore, teaching method skills and in particular the applied real-life skills demonstrated an average increase of 40% [p< 0. 01]. Participants’ confidence level increased, where 85 percent of the students stated that they felt prepared to face real-life situations. The external context proposed the cost-efficiency of the AI model as high [71. 4%] while the reusability [74. 3%]. Conclusion: It can be stated that integrating AI into training processes is highly beneficial to medical education, as it increases the levels of knowledge, skill, and confidence among students. To really understand something, it is often beneficial to learn with the help of simulations which are easily provided with the help of AI technologies. The implementation of AI into teaching practice at medical schools may be considered one of the ways of improving students’ readiness for clinical activity.